Implementation of Regional Regulation No. 1 of 2019 on Waste Management and Cleanliness in the City of Surabaya, Indonesia - Viktorius Dala; Willy Hardianto; Annisa Purwatiningsih; Rina Wulandari (Jurnal Ilmu Sosial dan Ilmu Politik (JISIP), 2025)
This study analyses the implementation of Surabaya City Regional Regulation No. 1 of 2019 concerning Waste and Cleanliness Management using Edward III's policy implementation analysis framework. The descriptive qualitative research method was conducted over a period of 6 months (January-June 2024) in Surabaya City, with the research locations being the Surabaya City Environmental Agency Office, the Trenggilis Prapen 88 Waste Disposal Site, and the waste management operational areas. The snowball sampling technique yielded 8 informants. Data was collected through semi-structured interviews (45-90 minutes per informant). The research results indicate that the implementation of waste management policies has been carried out using the 3R system (Reduce, Reuse, Recycle) and organic waste processing technology using larvae, but there is a significant gap in terms of resources. Policy communication has been conducted through routine socialisation, but field officers' understanding of the regulations is still limited. Limited infrastructure is the main obstacle, as waste collection carts and supporting equipment are inadequate, and maintenance responsibilities are left to field officers. The implementer's disposition shows a positive commitment to public-private collaboration in managing the Benowo landfill and methane gas processing system. The bureaucratic structure functions effectively with a clear division of tasks from the RT/RW level up to the TPA.Penelitian ini menganalisis implementasi Peraturan Daerah Kota Surabaya No. 1 Tahun 2019 tentang Pengelolaan Sampah dan Kebersihan menggunakan kerangka analisis implementasi kebijakan Edward III. Metode penelitian kualitatif deskriptif dilaksanakan selama 6 bulan (Januari-Juni 2024) di Kota Surabaya, dengan lokasi penelitian di Kantor Dinas Lingkungan Hidup Kota Surabaya, TPS Trenggilis Prapen 88, dan wilayah operasional pengelolaan sampah. Hasil penelitian menunjukkan bahwa implementasi kebijakan pengelolaan sampah telah berjalan dengan sistem 3R (Reduce, Reuse, Recycle) dan teknologi pengolahan sampah organik menggunakan larva, namun terdapat kesenjangan signifikan pada aspek sumber daya. Komunikasi kebijakan telah dilakukan melalui sosialisasi rutin namun masih terbatas pemahaman petugas lapangan terhadap regulasi. Keterbatasan sarana prasarana menjadi kendala utama, dimana gerobak pengangkut sampah dan peralatan penunjang tidak memadai serta tanggungjawab pemeliharaan diserahkan kepada petugas lapangan. Disposisi implementor menunjukkan komitmen positif dengan kolaborasi pemerintah-swasta dalam pengelolaan TPA Benowo dan sistem pengolahan gas metana. Struktur birokrasi berjalan efektif dengan pembagian tugas yang jelas dari level RT/RW hingga TPA.